Article RETRACTED due to manipulation by the authors Physical education learning outcomes of senior high school students based on gender and intellectual intelligence review - Zulbahri Zulbahri; Aldo Naza Putra; Hilmainur Syampurma; Indri Wulandari; Harifah Lawanis; Dessi Novita Sari; Weny Sasmitha; Siti Nurrochmah; Nurkadri Nurkadri; Baskoro Nugroho Putro; Gusliana HB; Harmanto Harmanto; et al. (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Abstract. This study examined the disparities in Physical Education (PE) learning Outcomes among high school pupils by considering their gender and intellectual aptitude. The study involved participants from a high school in Yogyakarta, selected using the Simple Random Sampling method. The data were then analysed using descriptive statistics and a two-way factorial inferential analysis of variance (ANOVA). The study divided the results into two groups based on their intellectual intelligence: low and high. In the low intellectual category, the average learning outcome for male students was 83.60. Meanwhile, the average for female students was 84.10. In the high intellectual intelligence category, the average results for male students were 85.30, while the average achievement for female students was 83.70. The ANOVA test for the intellectual intelligence variable yielded a p-value (Sig.) of 0.303, which is greater than the significance level of 0.05. This figure suggests that there is no statistically significant difference in students’ learning outcomes based on their level of intelligence, whether low or high. Similarly, the p-value of 0.383 for the gender variable was also greater than the significance level of 0.05, indicating no statistically significant variations in learning results. Additionally, the interaction effect between IQ and gender yielded a significance value of 0.100, which is greater than 0.05. It indicates no significant interaction between these two variables on the learning performance of high school students. The finding means that cognitive intelligence does not have a substantial impact on the performance of physical education (PE) among high school students. Moreover, there is no notable disparity in PE performance between male and female students, suggesting gender equality in both the opportunities and abilities in PE. Finally, the study found no notable correlation between gender and IQ levels in performance on intelligence tasks. These results diminish the importance of considering other criteria, such as physical aptitude, in evaluating PE performance and emphasize the need for comprehensive and inclusive physical education programs.